121k views
2 votes
How yall can help me out

How yall can help me out-example-1

2 Answers

2 votes

Answer: (b)

Explanation:

2√12 x 3√5 (numerator)

= (2x3)(√12x √5)

= 6√60

√30x √36

= √30 x 6

=6√30

Now,

6√60/6√30

We can cancel 6

So, it's √60/√30

= √60/30

= √ 2= 1.41 approx

Hope it helps!

3 votes

Answer:

Explanation:


(2√(12)*3√(5))/(√(30)*√(36))\\\\=(2*3√(12*5))/(√(30*36))\\\\=(6√(2*2*3*5))/(√(2*3*5*6*6))\\\\=(6*√(2)*√(2)*√(3)*√(5))/(6*√(2)*√(3)*√(5))\\\\=√(2)\\\\=1.41

User Stark Jeon
by
4.5k points